Indonesian Ocean Policy: Paradigm Shift in Strengthening Ocean Governance - Ade Maman Suherman; Aryuni Yuliantiningsih; Noer Indriati; Wismaningsih; Mohd Hazmi Mohd Rusli (Universiti Sains Islam Malaysia, 2024)
Indexed by WOS/SCOPUS/ERA